Dismal River [large type] - Dundee, Wayne D. (A Lone McGantry Western, 2023)
"Lone McGantry is a former Indian scout for the Army, now in his late thirties, a drifting horse wrangler, cowboy and guide. He's not fully ready to settle down but leaning gradually toward that lifestyle if he could find the right conditions. The Nebraska Sandhills of the 1880s are a vast, untamed expanse of treeless, rolling hills scoured by harsh wind and blistering sun. Into this rugged landscape former Indian scout Lone McGantry reluctantly agrees to lead an expedition of explorers and adventurers headed by an English lord. The hardships of the environment soon become secondary, however, when other threats - both from within and without - overtake the expedition. Deceit, betrayal, stampeding buffalo, a raging grass fire, and a band of ruthless marauders all must be dealt with. The very survival of the expedition is at stake. Lives will be lost and the banks of the Dismal River will be scorched and stained by blood before the ordeal is finished."--